2022
DOI: 10.3389/fenvs.2021.818402
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Changbai Mountain Topography on the Extreme Precipitation From Super Typhoon Maysak

Abstract: Based on hourly gridded precipitation data (0.1°) calculated by the China Meteorological Administration (CMA), the European Centre Medium-Range Weather Forecasts (ECMWF) reanalysis data, and microwave measurements, this paper investigated the extreme precipitation induced by the Typhoon Maysak in Northeast China (September 2020), using the Advanced Research dynamic core of the Weather Research and Forecasting Model (WRF-ARW). The study focused on Changbai Mountain topography and the extreme precipitation in Ji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Human activities have led to global warming and increased tropical humidity, increasing precipitation in the H-Plain [95]. Human activities contribute more significantly than natural climate change to the variance in maximum daily rainfall (about 10%).…”
Section: Discussionmentioning
confidence: 99%
“…Human activities have led to global warming and increased tropical humidity, increasing precipitation in the H-Plain [95]. Human activities contribute more significantly than natural climate change to the variance in maximum daily rainfall (about 10%).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid advancement of computer technology, various numerical models have been widely employed to investigate the orographic effects on regional precipitation. Previous studies have shown that the uplifting effect of topography enhances positive vorticity on the windward slopes, fostering accelerated vertical upward motion [5]. On the other hand, the obstructive effect of topography alters the wind direction at the bottom of the Northeast cold vortex, forming new convective clouds on the windward slopes and intensifying precipitation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that large-scale circulation patterns, such as the North Atlantic Oscillation, Madden Julian Oscillation, and El Niño-Southern Oscillation, synoptic-scale disturbances, mesoscale convective systems, boundary layer convergence, and local terrain, all play pivotal roles in the dynamics of extreme precipitation [2][3][4]. Additionally, monsoonal circulation, moisture transport, and the downward propagation of high potential vorticity also influence the formation of extreme precipitation [5][6][7]. Nonetheless, predicting extreme precipitation accurately remains challenging due to the complex interaction between various physical processes across different spatial and temporal scales [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In early and late summer, the water vapor anomaly mainly converges in the southwest during strong NECVI years [19]. Low tropospheric relative humidity (RH) is a prominent environmental factor during the monsoon season [22] and is influenced by the effect of the terrain on the NECVHR [23,24].…”
Section: Introductionmentioning
confidence: 99%